2005
DOI: 10.2337/diabetes.54.10.2968
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Insulin on Methionine and Homocysteine Kinetics in Type 2 Diabetes With Nephropathy

Abstract: Although hyperhomocysteinemia, an independent cardiovascular risk factor, is common in type 2 diabetes with nephropathy, the mechanism(s) of this alteration is not known. In healthy humans, hyperinsulinemia increases methionine transmethylation, homocysteine transsulfuration, and clearance. No such data exist in type 2 diabetes either in the fasting state or in response to hyperinsulinemia. To this purpose, seven male type 2 diabetic patients with albuminuria (1.2 ؎ 0.4 g/day, three with mild to moderate renal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
51
2
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(58 citation statements)
references
References 51 publications
2
51
2
2
Order By: Relevance
“…Ultimately, studies that focus on the measurement of metabolic flux through these pathways, similar to what has been recently reported (10,11), needs to be performed to definitively evaluate the effect of diabetes. Recently, a kinetic study with human subjects (51) demonstrated that transmethylation, homocysteine transsulfuration, and clearance of homocysteine were significantly reduced in type 2 diabetes with nephropathy.…”
Section: Discussionmentioning
confidence: 99%
“…Ultimately, studies that focus on the measurement of metabolic flux through these pathways, similar to what has been recently reported (10,11), needs to be performed to definitively evaluate the effect of diabetes. Recently, a kinetic study with human subjects (51) demonstrated that transmethylation, homocysteine transsulfuration, and clearance of homocysteine were significantly reduced in type 2 diabetes with nephropathy.…”
Section: Discussionmentioning
confidence: 99%
“…In disease condition, such as in diabetic nephropathy, Hcy disposal and clearance are impaired and therefore accumulate in the body, resulting in increase of plasma and tissue levels of Hcy (43). This, in turn, causes renal microvascular impairment and vasoconstriction (37), which lead to renal volume retention and further accumulation of Hcy (38).…”
Section: K Wt 2k Wtmentioning
confidence: 99%
“…In humans, studies in vivo have been restricted to plasma kinetics (1,24,37) but without knowing if these reflect common responses across all tissues or are dominated by just a few organs. From more detailed studies in rodents, liver, kidney, and pancreas are considered the main sites of methionine cycle activity, based on measurements in vitro of the enzyme activities of betaine homocysteine methyltransferase (BHMT) and methionine synthase (MS; N-5-methyltetrahydrofolate transferase) (41), but this does not mean they have the same end points of homocysteine metabolism.…”
mentioning
confidence: 99%